The Relationship between Microglial Activation and MS-Related Fatigue : a TSPO-PET Study - Hassanain, Eman (My University, 2022)
Background and Objectives. Fatigue is one of the common and disabling symptoms of MS. However, there is no definite interpretation of its mechanism. One of the proposed causes of the fatigue onset involves microglial activation, although this has been rarely examined. Therefore, the aim of this study was to assess the microglial activation role in MS-related fatigue using the TSPO-PET imaging technique. Methods. The study cohort included 25 MS patients and 10 healthy controls. Fatigue was measured using the Fatigue Scale for Motor and Cognitive Functions (FSMC), which provided total, cognitive, and motor scores. All participants were imaged using [11C]-PK11195 TSPO-PET and MRI. The distribution volume ratio (DVR) was used to evaluate the amount of [11C]-PK11195 binding in the region of interests (ROIs). Results. Patients with fatigue had a significantly higher microglial activation in the NAWM (1.22 ± 0.03 vs. 1.18 ± 0.03; p < 0.05) and thalamus (1.36 ± 0.07 vs. 1.31 ± 0.03; p < 0.01) than healthy controls. Cognitively fatigued patients had significantly higher activation in the thalamus than non-fatigued patients (1.37 ± 0.06 vs. 1.31 ± 0.07; p = 0.03), and motor fatigued patients had significantly higher activation in the NAWM, cortical gray matter, thalamus, and whole brain than healthy controls (1.21 ± 0.04 vs. 1.18 ± 0.03; p < 0.05, 1.24 ± 0.04 vs. 1.22 ± 0.04; p < 0.05, 1.36 ± 0.07 vs. 1.31 ± 0.03; p < 0.05, and 1.21 ± 0.02 vs. 1.19 ± 0.02; p < 0.05, respectively). A significant negative correlation was found between the corpus callosum (CC) DVR values and total (R = -0.44, p = 0.027), cognitive (R = -0.42, p = 0.034), and motor (R = -0.45, p = 0.025) fatigue scores. Conclusion. Microglial activation in the thalamus and NAWM might have a role in the pathogenesis of MS-related fatigue. Further evaluation of the correlation between fatigue scores and microglial activation in the corpus callosum is warranted.
Keywords: Multiple Sclerosis, MS-related fatigue, microglial activation, TSPO-PET, [11C]-PK11195